Numerical analysis and experimental visualization of phase change material melting process for thermal management of cylindrical power battery - Yang, Huan (2020)
Organic phase change materials (PCMs) have been of increasing interest in battery thermal management due to their high latent heat and excellent cycling stability. This paper reports both numerical analysis and visualization experiments for the melting process of paraffin PCM surrounding a cylindrical power battery. Specifically, two different housing materials are considered, one made of metal and the other made of acrylics. For the metal housing case, the PCM exhibits a melting front isolated both from the battery and housing wall with accelerated melting in the B∼C stage, accounting for the isothermal temperature plateau observed in both the numerical modeling and experimental measurements. For the acrylic housing case, the unmelted PCM instead adheres to the inner wall of housing all the way, melting at the rate slower than the metal housing case. In both housing cases, the numerically predicted liquid fractions are found to agree with our experimentally visualized results. The battery top to bottom temperature variation is also examined with regard to the melting process. Moreover, the instantaneous Nusselt number is obtained to identify the different heat transfer characteristics in the different melting stages.